Mecanismos do desejo: o gótico e a ficção-científica em The Infernal Desire Machines of Doctor Hoffman - Gomes, Emannuel Goncalves [UNIFESP] (2019)
Throughout her work, Angela Carter (1940-1992) established intertextual relations with multiple literary traditions. The Infernal Desire Machines of Doctor Hoffman (1972), her sixth novel, constitutes a turning point in the author’s career, mixing forms and themes present in both her early and later stages of writing. Taking this as a starting premise, this thesis intends to search a possible perspective concerning Carter’s manipulations and subversions of the Gothic and science fiction in literature. With this in mind, I try to understand how she reads and incorporates them in the construction of her text, as well as their inherent relation to the duality between authoritarian pragmatism and the chaotic impulses of the unconscious as they are portrayed in the novel. Therefore, I propose to analyze the characters, the plot and the allegories utilized by Carter against the background of their relations and the author’s literary project.